2010
DOI: 10.1111/j.1600-0765.2010.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Root surface conditioning with bone morphogenetic protein-2 facilitates cementum-like tissue deposition in beagle dogs

Abstract: Running titleCementum-like tissue formation on BMP-applied root surface. Key wordsBMP-2; Root dentin surface conditioning; cementum-like tissue; dogs Correspondence addressHirofumi MIYAJI. Department of Periodontology and Endodontology, Division of Oral Health Science, HokkaidoUniversity Graduate School of Dental Medicine, N13 W7 Kita-ku, Sapporo 060-8586, Japan. AbstractBackground and objective: Modification of the root surface may play an important role in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Besides, all groups employing the barrier membrane indicated more cementum regeneration than the control group. These findings were consistent with the previous studies (Miyaji et al, ; Ribeiro et al, ). Notably, the height of cementum was lower than the height of the bone in the BMP‐2/BioCaP + barrier membrane group.…”
Section: Discussionsupporting
confidence: 94%
“…Besides, all groups employing the barrier membrane indicated more cementum regeneration than the control group. These findings were consistent with the previous studies (Miyaji et al, ; Ribeiro et al, ). Notably, the height of cementum was lower than the height of the bone in the BMP‐2/BioCaP + barrier membrane group.…”
Section: Discussionsupporting
confidence: 94%
“…self‐reorganization) is extremely difficult to control completely. For example, bone morphogenetic protein strongly promotes bone augmentation, but regeneration of the periodontal ligament is rarely observed, and ankylosis is frequently detected . In contrast, creation of fibrous tissue, such as periodontal membrane, and the absence of ankylosis were apparent in this study.…”
Section: Discussionmentioning
confidence: 51%
“…38,39 The application of nanoparticle-modified structures might increase the surface area and subsequent signaling molecule adsorption, thereby improving cell behaviors. [10][11][12]40 The present SEM observation in 1 µg/mL GO scaffold demonstrated that wrinkling structures covered by GO sheets were formed frequently on the collagen strut of the scaffold. The GO sheet possesses many functional groups including hydroxyl (OH), epoxy (C-O-C), and carboxyl (COOH) species on its surface.…”
mentioning
confidence: 51%